Habitat selection by European badgers in Mediterranean semi-arid ecosystems (Journal of Arid Environments, 2012)
We studied the habitat selection patterns of badgers Meles meles (Linnaeus, 1758) in Mediterranean semiarid ecosystems. Fifty-seven plots were sampled in two semi-arid regions of Spain. In each plot, badger latrines were located along 2.6 km transects. The number of badger latrines per km was used as a surrogate of badger abundance and as an index of habitat selection by badgers. For each plot, a series of environmental variables were measured at two spatial scales. These variables were related to land use and vegetation formation parameters that are considered potentially important for habitat requirements (i.e., food and shelter). The habitat selection model was carried out using generalised linear models (GLM) and an information-theoretic approach. Results indicated that badgers prefer fruit orchards, and shrub and rock-covered areas, which provide additional trophic and shelter resources, and avoid intensively cultivated ﬁelds and human settlements. We conclude that badger conservation in semi-arid environments of the Iberian Peninsula requires the existence of fruit orchards and the limitation of human development. Policies restraining agriculture intensiﬁcation would encourage traditional or new non-intensive agricultural practices and increase shrub-patch availability, which would beneﬁt this species.

Environmental constraints at the edge of a species distribution, the Eurasian badger (Meles meles L.): a biogeographic approach (JOURNAL OF BIOGEOGRAPHY, 1999)
Aim This paper describes the distribution pattern (occurrence) of badgers (Meles meles L. 1758) in a Mediterranean mountain area of central Spain, in relation to landscape characteristics and climatic data. We test the fit of the badger occurrence pattern to the niche hypothesis predictions. Location We sampled twenty-four survey plots randomly distributed in the mountains of central Spain (Sierra de Guadarrama, Madrid): ten in the north and fourteen in the south slopes. All habitat types and climatic conditions typical of central Spain can be found. Methods The ocurrence of badgers ill the plots were recorded through an exhaustive search of setts and latrines in four different (and evenly spaced) points in each plot. The index of occurrence was made by dividing the number of positive points (badger presence) by the total number of points sampled (four in all plots). Landscape patterns (% type of habitat in each plot) were obtained from detailed maps and climate data from meteorological stations placed in the plot. We analyse the contribution of landscape variables and climate data to explain the differences in badger occurrence through Pearson correlations and fixed one-way ANCOVA with climatic data as fixed factor, vegetation cover as covariates and badger occurrence as response variable. Additionally, we use an one-way ANOVA to check the differences in occurrence between north and south plots with the location of each plot as fixed factor. Results The results indicate that the badger is more abundant in rainy areas of the mountains, and in open landscapes vegetated by ash-tree forests than in closed landscapes vegetated by helm oak forests. In addition, the species is more abundant in the northern plots than in the southern ones. Northern plots were homogeneous areas characterized by their open landscape and wet climate, while southern plots were characterized by their dry climate and closed landscapes. In addition, climate (measured as summer rain) is more determinant than habitat type (holm oak cover) to explain the pattern of badger occurrence. Main conclusions Overall, we consider that the typical Mediterranean landscapes are poor habitats for badgers due to changes in the environmental conditions associated with. concomitant changes in food resources. These data support the niche hypothesis to explain the changes in abundance or occurrence close to the edge of the distribution of species, and in particular, in Palearctic species in the Mediterranean area.

Roe deer habitat selection in Spain: constraints on the distribution of a species (Canadian Journal of Zoology, 1998)
This study analyzes the role of summer habitat selection in determining the distribution of a population of roe deer (Capreolus capreolus L.) in central Spain, where surplus individuals have emigrated from mountains to the surrounding plateaus during the last decade. The species was more abundant in the mesic mountain forests (Scots pine (Pinus sylvestris), Pyrenean oak (Quercus pyrenaica)) than in the xeric, sclerophyllous holm oak (Quercus ilex) forests of surrounding plateaus. Roe deer prefer patches occupied by brambles (Rubus spp.) and rose bushes (Rosa spp.) and patches with higher cover on pastures and moors (Erica spp. and Calluna spp.). These vegetation types are linked to moist soils in the Mediterranean zone, indicating that roe deer prefer the moister, more productive patches. Roe deer actively selected productive patches covered by leguminous shrubs (Sarothamnus, Retama) and rejected poor patches covered by Cistus ladanifer and Cistus laurifolius (two shrubs that produce chemicals toxic to other plants). Low summer primary productivity of xeric, sclerophyllous forests can explain the low abundance of roe deer in these forests. This supports the view that habitat constraints limit numbers and distribution of this Palaearctic species at the southern edge of its range.
doi: 10.1139/z98-065